2012
DOI: 10.5586/asbp.2012.013
|View full text |Cite
|
Sign up to set email alerts
|

Soil acid phosphomonoesterase activity and phosphorus forms in ancient and post-agricultural black alder [Alnus glutinosa (L.) Gaertn.] woodlands

Abstract: IntroductionSeveral phosphatases are involved in the hydrolysis of organic P compounds but the major role in the organic phosphorus mineralization process is attributed to the phosphomonoesterases. Acid phosphomonoesterase enzymes are the dominant group of enzymes involved in organic P mineralization in acidic soils [1]. These enzymes are produced mainly by plants and fungi and to a lesser degree by bacteria. The level of acid phosphomonoesterase secreted by plant roots has been shown to differ significantly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
(48 reference statements)
3
15
0
1
Order By: Relevance
“…Negative correlation confirms the results reported by others (Vong et al, 2004;Kotkova et al, 2008) that a high content of sulphates in soil decreases the activity of arylsulphatase. A lack of the correlation between the content of available phosphorus and the activity of phosphatases is confirmed by earlier reports by Orczewska et al (2012). Significant at p < 0.05; P E-R -available phosphorus, S-SO 4 -2 -sulphur Conclusions 1.…”
Section: Resultssupporting
confidence: 72%
“…Negative correlation confirms the results reported by others (Vong et al, 2004;Kotkova et al, 2008) that a high content of sulphates in soil decreases the activity of arylsulphatase. A lack of the correlation between the content of available phosphorus and the activity of phosphatases is confirmed by earlier reports by Orczewska et al (2012). Significant at p < 0.05; P E-R -available phosphorus, S-SO 4 -2 -sulphur Conclusions 1.…”
Section: Resultssupporting
confidence: 72%
“…Kinetics studies have indicated that orthophosphate ions, which are the product of the reaction that is conducted by the phosphatases, are a competitive inhibitor of their activity in soil (Hui et al 2013). Other studies have found a significant correlation between phosphatase activity and the available P content (Orczewska et al 2012). In this study, similar to observation made by Wang et al (2011), no significant relationship was observed between any P form and phosphatase activity, which suggested that P may not limit the system that was studied and that some other masking factors such as site geology may influence enzyme production and activity (Olander and Vitousek 2000).…”
Section: Correlations Among the Properties Studiedsupporting
confidence: 87%
“…Some studies have been devoted to examining the relationship between different forms of soil P and the activity of enzymes of the P cycle and the results have been varied with positive, negative, or no correlations being reported (Miller et al 2001;Wang et al 2011;Orczewska et al 2012). A significant but negative relationship between both of these parameters is often shown in soil on which P fertilizers are applied, and/or in naturally fertile soil (Miller et al 2001).…”
Section: Correlations Among the Properties Studiedmentioning
confidence: 99%
“…From a practical point of view, historical ecology provides a valuable template for nature conservation and restoration planning: firstly, the ecological continuity of habitats affects recent biodiversity levels [7,8], and secondly, historical ecology allows the setting of restoration references and targets as well as providing an insight into the appropriate location and distribution of habitats to develop landscape-level conservation strategies [3,9,10]. Thirdly, historical land use legacies (e.g., changes in chemical properties of soil) influence site properties by determining their potential for restoration [7,9,11,12].…”
Section: Introductionmentioning
confidence: 99%